Architectural elements, geometry, and magmatism of the Sub-Saharan Western African passive margin basins: Seismic and gravity data integration. (December 2022) - Aragão, Maria Alice Nascimento Fagundes de; Szameitat, Luizemara Soares Alves; Figueiredo, Antonio Manuel Ferreira de; Heilbron, Monica; Manatschal, Gianreto
Abstract: The Western African Sub-Saharan continental margin includes a large region from Cameroon to South Africa comprising distinct margin types – magma-rich, magma-poor and transform margins. The integrated study of geological, seismic and potential field data allows the mapping of a structural framework subdivided in proximal, necking, distal, outer and oceanic domains, characterized by a set of comparable architectural elements and magmatism. These key domains display a strong and consistent continuity along the continental margin. Longitudinal transitional regions occur in a gradual way, but interactions between structural domains along transversal section may also occur, displaying spatial and temporal overprints. Because of this complexity, the outer domain that is the key feature in the magma-rich margin, tends to disappear northwards where the distal and proximal domains of the magma-poor segments become the most important domains of the margin. In the north of Gabon Basin, it is observed both the reappearance of the outer domain and the reworking of the distal domain by fracture zones. The basement of the distal domain within the magma-poor margin is interpreted as made by a hyperextended continental crust but with magmatic additions. Finally, the new proposed continent-ocean boundary (COB) in the region of the Namibe Basin (transitional zone between magma-rich and magma-poor margins) achieves a best fit in a reconstruction model with the limits recognized at the South America side. The results will imply in a drastic reduction on the gap proposed by other recent reconstruction models and also minimize the intraplate deformation required by some other models. Highlights: The Western African Sub-Saharan continental margin comprises distinct type: magma-rich, magma-poor and transform margins. Integrated geological, seismic, and gravity data allows the mapping of the structural framework throughout margin segments. Longitudinal transitional regions occur in a gradual way. The new proposed continent-ocean boundary in the region of Namibe Basin achieves a best fit in a reconstruction model. Obtained results imply in a drastic reduction on the gap and minimizing the intraplate deformation required.